2008
DOI: 10.1111/j.1365-3164.2008.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of threshold concentrations of multiple allergenic extracts for equine intradermal testing using normal horses in three seasons

Abstract: Forty-one normal horses were evaluated for reactivity to intradermally injected aqueous allergens to determine allergen threshold concentrations (TC), with potential relevance to equine intradermal testing (IDT). Horses were tested three times over 1 year to assess seasonal variation in reactivity, using three to five serial dilutions of 27 allergens each time. Injection sites were evaluated after 15 min, 1 h, 4 h and 24 h. The highest allergen concentration at which < 10% of horses demonstrated positive react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
34
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 33 publications
10
34
2
Order By: Relevance
“…30,42 Allergen selection. However, some studies indicate that different concentrations may be necessary for different antigens (e.g., 60-250 PNU/mL for most insects and dust mites).…”
Section: Intradermal Allergy Testingmentioning
confidence: 99%
“…30,42 Allergen selection. However, some studies indicate that different concentrations may be necessary for different antigens (e.g., 60-250 PNU/mL for most insects and dust mites).…”
Section: Intradermal Allergy Testingmentioning
confidence: 99%
“…Although raising horses in specific pathogen‐free conditions has been done, this is extremely costly. Threshold concentrations have been arbitrarily defined as the concentration where <10% of nondiseased animals have a positive reaction . It is proposed that if a greater percentage of healthy animals react to the allergen concentration used, then the reaction should be considered a false‐positive result because the allergen was acting as an irritant …”
Section: Introductionmentioning
confidence: 99%
“…Equine studies for TCs are limited, both in number and in scope. Five studies have examined IDT TCs in horses . Three studies examined TCs of insect extracts and the other two reported the seasonal variation of TCs for pollen, insect, mould and mite extracts .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One pilot study published as an abstract found house dust mite antigen and mites similar in appearance to house dust mites in a limited number of horse barn dust samples, 1 but this has not been studied further. Despite this, the response to dust mite antigens is frequently assessed by intradermal or serological testing of atopic horses, in a similar fashion to allergy tests in atopic humans, dogs and cats 2–4 . Some atopic horses exhibit positive reactions on intradermal testing with dust mite allergens, although it is controversial whether this represents true allergy to house dust mites, irritant reactions or cross‐reactivity with other true allergens 2–4 …”
Section: Introductionmentioning
confidence: 99%